Karakterisik Organoleptik, Fisik, dan Kimia Biskuit Tersubstitusi Tepung Bekatul dengan Penambahan Tepung Bit Merah (Beta vulgaris) - Dewi Hilmiatul Mufidah (Fakultas Teknologi Pertanian Universitas Jember, 2024)
Biscuits are wheat-based pastries that are currently developed using local ingredients to add functional value. The local ingredient used to replace wheat flour in this study is rice bran with the addition of red beet (Beta vulgaris) to reduce the unattractive color of rice bran and add functional value. This study aims to determine the effect of the percentage of rice bran flour with the addition of red beet flour as a substitute for wheat flour on the organoleptic, physical and chemical characteristics of biscuits. In addition, this study aims to get the best treatment in biscuits substituted with bran flour with the addition of red beet flour. The ratio of wheat flour and rice bran flour in percent is 75:25, 60:40, 50:50. The concentration of red beet flour was 0%, 2.5%, 5%, and 10%. Chi-square hedonic test showed that the concentration of red beet had a significant effect on color, texture, taste, and overall. However, it did not significantly affect the aroma hedonics. The results of two-way ANOVA analysis showed that the ratio of wheat and rice bran and the addition of red beet flour had a significant effect on the physical characteristics of color, texture and antioxidant activity. Biscuits with a ratio of 75 % wheat flour, 25 % rice bran flour, and 10% red beet flour were the best samples with chemical test values of antioxidant activity of 24.94 µg/mL, moisture content of 7.2%, ash content of 2.05%, fat 20.04%, protein 11.4%,
Reuploud file repositori 13 Apr 2026_Firli_tata
Keywords: Biscuits; rice bran flour; red beet flour